The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1099/ijs.0.045815-0
|View full text |Cite
|
Sign up to set email alerts
|

Algibacter aquimarinus sp. nov., isolated from a marine environment, and reclassification of Pontirhabdus pectinivorans as Algibacter pectinivorans comb. nov.

Abstract: Algibacter aquimarinus sp. nov., isolated from a marine environment, and reclassification of Pontirhabdus pectinivorans as Algibacter pectinivorans comb. nov. T , was isolated from seawater collected from Gwangyang Bay, Republic of Korea. The isolate required sea salts for growth. Gliding motility was observed. Flexirubin-type pigments were absent. Major cellular fatty acids (.10 % of the total) were iso-C 15 : 0 , iso-C 17 : 0 3-OH, iso-C 15 : 1 G, C 16 : 0 , iso-C 15 : 0 3-OH and C 18 : 0 . The main polar li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…The fatty acid profiles of the three strains grown and analysed under identical conditions in this study were similar, but there were also differences in the proportions of some fatty acids. A. mikhailovii LMG 23988 T was characterized by having a higher amount of summed feature 3 (C 16 : 1 v7c and/or C 16 : 1 v6c), which was also shown in the study of Park et al (2013). Strain WS-MY9 T contained phosphatidylethanolamine (PE) and two Naphthol-AS-BI-phosphohydrolase…”
Section: Strain Ws-my9mentioning
confidence: 61%
See 1 more Smart Citation
“…The fatty acid profiles of the three strains grown and analysed under identical conditions in this study were similar, but there were also differences in the proportions of some fatty acids. A. mikhailovii LMG 23988 T was characterized by having a higher amount of summed feature 3 (C 16 : 1 v7c and/or C 16 : 1 v6c), which was also shown in the study of Park et al (2013). Strain WS-MY9 T contained phosphatidylethanolamine (PE) and two Naphthol-AS-BI-phosphohydrolase…”
Section: Strain Ws-my9mentioning
confidence: 61%
“…The second species of the genus Algibacter, Algibacter mikhailovii, was subsequently described following isolation from a sea urchin (Nedashkovskaya et al, 2007). Recently, Algibacter aquimarinus has been described and Algibacter pectinivorans reclassified as a member of the genus Algibacter (Park et al, 2013). In this study, a novel bacterial strain, designated WS-MY9 T and isolated from brown algae collected from a reservoir located on Wando, an island of South Korea, is described.…”
mentioning
confidence: 98%
“…Aquimarina addita JC2680 T (HM475137) with the one formed by the genera Hyunsoonleella (Yoon et al, 2010) and Jejuia (Lee et al, 2009), within a cluster encompassing the genera Hyunsoonleella, Jejuia and Marinivirga and two species of the genus Algibacter (Park et al, 2013b). Topologies of the maximum-parsimony and maximum-likelihood trees were nearly identical to the one shown by the neighbour-joining tree (Figs S1 and S2 available in IJSEM Online).…”
Section: Cellulophaga Fucicola Nn015860 T (Aj005973)mentioning
confidence: 75%
“…The type species Algibacter lectus and the species Algibacter mikhailovii (Nedashkovskaya et al 2007) included strains from seaweed or strains that showed agarolytic activity. Recently, we reclassified a non-agarolytic marine bacterium Pontirhabdus pectinivorans (Yi et al, 2011) in this genus as Algibacter pectinivorans and described a novel species of the genus, Algibacter aquimarinus (Park et al, 2013b). During a study on the microbial diversity of the seawater of Gwangyang Bay, two yellow-pigmented flavobacterial strains, designated KYW560…”
mentioning
confidence: 99%